Regional trade blocks: implications for public administration reform in the United States - Lynch, Thomas D; Sekwat
The article analyzes the new world reality of emerging regional economic trade blocks and its implications for modern public adminisrtration in industrialized countries including the United States. The international economic competition is rapidly becoming the driving reality in shaping economic and political world relations. Gives the present trend in world trade patterns and discusses three trade blocks which include the European Community, North America and Pacific Rim. Author discusses the future of multilateral trade and argues that nations that are competitive will have higher standards of living. Government at all levels in a nation will be key determinant of a nation's ability to compete effectively
Keywords: Reform; Public Administration; Regional Trade Blocks; International Economic Relations - YSA